Police Control Over Radical Groups - Sutrisno, Sutrisno; Syafrudin, Syafrudin (Opción, 2019)
Differing from the Orde Baru era, in the Reformation era the police were limited on handling radical groups regarding the compatibility of democracy. Controlling radical groups is a long chain of prevention and counter-terrorism. That terror (terrorism) is the fruit of radicalism; although not all groups of radical or radical actors have always terrorized. The purpose of the paper is tracing how police identified radicalism; and how the police control the rad- ical groups. This was done using the Focused Group Discussion method in three Regional Police (Polda), containing 15 sub-regional police. The findings, to identify radical groups, is based on the definition that is constructed by the social environment. To distinguish radical groups, police base this on “social construction”. So, it is not as done by the Crime Investigation Section that has a strict size in the legal norm. In fact, “social construction” is moving faster than the formal legal norms that the criminal investigation has in common.